Evaluation of beneficial effects of addition of intramuscular human tetanus immunoglobulin to intrathecal therapy in the treatment of tetanus - Mahajan, Sanjiv (International Journal of Advances in Medicine, 2017)
Background: The treatment of tetanus has evolved from supportive management only to specific treatment to neutralize the tetanus toxins – tetanospasmin & tetanolysin. Human Tetanus Immunoglobulin (HTIg) is a large molecule and cannot cross the blood brain barrier. Introduction of intrathecal therapy considerably decreased mortality in the disease. Combined administration of intramuscular and intrathecal HTIg should neutralize the tetanus toxins in the circulation and central nervous system simultaneously. The study was done to detect beneficial effects of adding intramuscular HTIg to the intrathecal therapy. Methods: 125 patients of tetanus were randomized to two groups. Study group was given intrathecal plus intramuscular HTIg while control group was given intrathecal HTIg alone. Each group was subdivided into three grades according to severity. Mortality rate and three sequential recovery parameters i.e. duration of spasms, shift to oral therapy and duration of hospital stay were measured. Results: No significant difference in mortality was found. However, in patients who survived, the addition of intramuscular HTIg lead to a benefit of 2.07, 2.67 & 2.31 days in mild, moderate & severe grades respectively in the duration of spasms. Further, it became possible to start oral therapy 2.13, 1.6 & 1.8 days earlier in mild, moderate & severe tetanus. Duration of hospital stay was reduced by 3.87 days, 2.36 days and 3 days in mild, moderate and severe tetanus respectively. Conclusions: Though the addition of intramuscular HTIg to intrathecal therapy in tetanus does not confer any survival benefit, it causes faster recovery in patients who survive.